Bleaching efficiency of low concentration hydrogen peroxide on Sesbania Grandiflora - Loo, Jazween (2020)
This research was aimed to evaluate the bleaching effectiveness of low concentration hydrogen peroxide on Sesbania grandiflora pulp and the effect on its mechanical properties (including bursting strength, tensile strength, tearing resistance and folding endurance). The main purpose of bleaching is to remove residual lignin and increase the brightness of the paper. However, under a certain premise, bleaching causes the weakening of the fibre strength and the interfiber bonding strength thus affect the quality of the paper. Hydrogen peroxide is a relatively mild bleaching agent which is suitable for Sesbania grandiflora short fibre. Low concentration of hydrogen peroxide bleaching treatment can achieve the objective of eliminating the lignin as well as preventing fibre damage. Sesbania grandiflora pulp was treated with 1 wt% hydrogen peroxide under controlled condition while bleaching duration (0, 20, 40, 60 minutes) of the hand sheet as a manipulated variable. As a result, 40 minutes of bleaching duration will give the pulp maximum bursting strength and tensile strength, minimum tearing resistance and satisfactory brightness and opacity. In the other hand, 60 minutes of bleaching produces pulp with maximum brightness with a slight drop in mechanical properties including bursting strength and tensile strength due to fibre degradation. As a summary, 40 minutes of bleaching treatment is the optimum bleaching duration on Sesbania grandiflora pulp. This research is valuable as a reference of Sesbania grandiflora becoming the raw material in the pulp and paper industry since the research of the field is still at an early stage and the information is limited at the time.